2019
DOI: 10.1097/md.0000000000015390
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia for patient with Fahr's syndrome

Abstract: Rationale:Fahr's syndrome (FS) is a rare neurological and psychiatric disorder characterized by bilateral brain calcifications when a secondary cause of the calcification is found.Patient concerns:A 53-year-old female patient diagnosed with FS for laminectomy because of ossification of posterior longitudinal ligament. She had a history of generalized tonic-clonic (GTC) seizure and medication with anticonvulsant drugs. She had gait disturbance, spasticity, bradykinesia, and diffuse calcifications in the basal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Previous animal experiments have shown that low magnesium or magnesium-free perfusate can directly stimulate the hippocampal slices and olfactory bulb slices of rats, leading to spontaneous epileptic discharges [7][8][9]. Some studies have indicated that epileptic patients have significantly lower levels of magnesium in their plasma and serum compared to control groups [10,36]. Furthermore, MgSO 4 infusion has been successfully used to help one drug-resistant epilepsy patient with normal MRI performance and two patients with Alpers syndrome caused by mtRNA polymerase mutations to improve their status epilepticus [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal experiments have shown that low magnesium or magnesium-free perfusate can directly stimulate the hippocampal slices and olfactory bulb slices of rats, leading to spontaneous epileptic discharges [7][8][9]. Some studies have indicated that epileptic patients have significantly lower levels of magnesium in their plasma and serum compared to control groups [10,36]. Furthermore, MgSO 4 infusion has been successfully used to help one drug-resistant epilepsy patient with normal MRI performance and two patients with Alpers syndrome caused by mtRNA polymerase mutations to improve their status epilepticus [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes FS associates with cerebrovascular diseases and myopathies. 9,10 Before the advent of CT scan, the diagnosis of FS was based on X-rays of the skull and autopsy. Today, brain CT is the investigation of choice for the detection of intracerebral calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical signs that can be encountered are convulsions, dementia, syncope, vertigo, dysarthria, headache, orthostatic hypotension, and neuropsychiatric disorders such as hallucinations, delusions, anxiety, mania, and depression. Sometimes FS associates with cerebrovascular diseases and myopathies 9,10 …”
Section: Discussionmentioning
confidence: 99%